2012
DOI: 10.1029/2012ja017563
|View full text |Cite
|
Sign up to set email alerts
|

Artificial ducts caused by HF heating of the ionosphere by HAARP

Abstract: [1] We report on satellite observations of plasma density enhancements (ducts) in the topside ionosphere during four HAARP/BRIOCHE campaigns during 2009-2010. Artificial ducts, caused by high-power HF radio wave injections from the HAARP transmitter toward the magnetic zenith, are detected by the DEMETER and DMSP satellites on a regular basis when there is a perceptible ionospheric F 2 peak density. Overall, the plasma density enhancements detected between 0930 and 1230 LT varied from 3-13%, while those during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 21 publications
(31 reference statements)
3
39
0
2
Order By: Relevance
“…The model was generally found to be in agreement with observations, except that SAMI2 did not predict that "fine structure"-oscillations of the density about the expected mean with a scale length smaller than the width of the heating regionwould be present. Vartanyan et al [2012] has suggested that heating-driven enhancement of preexisting density irregularities could explain the formation of this fine structure. Ducts 1-3 likely represent fine structuring of the heating region due to the same process, as they are similar in both width and magnitude to the ducts previously identified by [Vartanyan et al 2012] under similar circumstances.…”
Section: Duct Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The model was generally found to be in agreement with observations, except that SAMI2 did not predict that "fine structure"-oscillations of the density about the expected mean with a scale length smaller than the width of the heating regionwould be present. Vartanyan et al [2012] has suggested that heating-driven enhancement of preexisting density irregularities could explain the formation of this fine structure. Ducts 1-3 likely represent fine structuring of the heating region due to the same process, as they are similar in both width and magnitude to the ducts previously identified by [Vartanyan et al 2012] under similar circumstances.…”
Section: Duct Characterizationmentioning
confidence: 99%
“…Vartanyan et al [2012] has suggested that heating-driven enhancement of preexisting density irregularities could explain the formation of this fine structure. Ducts 1-3 likely represent fine structuring of the heating region due to the same process, as they are similar in both width and magnitude to the ducts previously identified by [Vartanyan et al 2012] under similar circumstances.…”
Section: Duct Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the diffusion coefficient is larger at the upper region than lower region, a duct of electron upflows formed at the topside ionosphere. This phenomenon has been observed by Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) and DMSP satellites flying across the topside ionosphere of heating experiments [ Vartanyan et al ., ; Milikh et al ., , ]. Such pump‐induced plasma upwelling flow have also been detected by EISCAT during the Tromsø heating experiment and Sura heating facilities [ Rapoport et al ., , ; Frolov et al ., ; Kosch et al ., ].…”
Section: Discussionmentioning
confidence: 99%